PEDAGOGICAL OPPORTUNITIES OF THE GENDER SELFREALIZATION SKILLS DEVELOPMENT IN ADOLESCENT LEARNERS (Scientific journal of the Fergana State University, 2023)
This article analyzes the specifics of the formation of immunity against "mass culture" in adolescent students on the basis of a gender approach, thinking that adolescence is a complex, controversial period, the development of self-awareness and self-esteem during this period.